2020
DOI: 10.1038/s41598-020-71535-4
|View full text |Cite
|
Sign up to set email alerts
|

Sylvian fissure development is linked to differential genetic expression in the pre-folded brain

Abstract: The mechanisms by which the human cerebral cortex folds into its final form remain poorly understood. With most of the current models and evidence addressing secondary folds, we sought to focus on the global geometry of the mature brain by studying its most distinctive feature, the Sylvian fissure. A digital human fetal brain atlas was developed using previously obtained MRI imaging of 81 healthy fetuses between gestational ages 21 and 38 weeks. To account for the development of the Sylvian fissure, we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Brain folding occurs in different dimensions. The development of the sulci and gyri within a lobe is the result from biological and physical phenomena, ultimately bending the brain surface by tangential expansion; the folding of the frontal and temporal lobe over the insula, to form the Sylvian fissure, is a completely different event [ 19 ]. Bush et al previously suggested that the Sylvian fissure appears by convergence of the anterior and posterior poles of the embryonic telencephalon and proposed a convergence index for the adult brain, calculated as the Euclidean distance/transcortical distance ratio, that returns its highest values around the fissure [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain folding occurs in different dimensions. The development of the sulci and gyri within a lobe is the result from biological and physical phenomena, ultimately bending the brain surface by tangential expansion; the folding of the frontal and temporal lobe over the insula, to form the Sylvian fissure, is a completely different event [ 19 ]. Bush et al previously suggested that the Sylvian fissure appears by convergence of the anterior and posterior poles of the embryonic telencephalon and proposed a convergence index for the adult brain, calculated as the Euclidean distance/transcortical distance ratio, that returns its highest values around the fissure [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.pone.0245167.g003 form the Sylvian fissure, is a completely different event [19]. Bush et al previously suggested that the Sylvian fissure appears by convergence of the anterior and posterior poles of the embryonic telencephalon and proposed a convergence index for the adult brain, calculated as the Euclidean distance/transcortical distance ratio, that returns its highest values around the fissure [20].…”
Section: Discussionmentioning
confidence: 99%
“…Since 13 gw, cells from the subpallial neurons migrate into the insular cortex along the radial glial fascicle reaching the final configuration before birth ( 16 ). Mallela et al ( 17 , 18 ) found different gene expressions from the opercula to the insula resulting in the highest proliferation of the former allowing their growth over the insula. This different origin might explain the fact that the tracts that developed later connecting frontal, temporal, and parietooccipital regions ‘avoid crossing the insula', thus being located ventral or dorsal to it, and in some cases wrapping around it with specific curved patterns ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 13 gw, cells from the subpallial neurons migrate into the insular cortex along the radial glial fascicle reaching the final configuration before birth (16). Mallela et al (17,18) found different gene expressions from the opercula to the insula resulting in the highest proliferation of the former allowing their growth over the insula. This different origin might explain the fact that the tracts that developed later FIGURE 8 | An 18-year-old left-handed girl presented with medically refractory epilepsy that was symptomatic since the age of 3 years due to a perinatal stroke in the territory of the left middle cerebral artery.…”
Section: Figure 5 | (A)mentioning
confidence: 99%
“…Moreover, the gene expression profile of the pre-folded brain has been reported to be significantly different in the developing opercular cortex compared to the insular cortex (Mallela et al, 2020).…”
Section: Opercularization and Sulcation Show Different Dynamicsmentioning
confidence: 99%